The role of the Hippo/YAP pathway in the physiological activities and lesions of lens epithelial cells - Shumei Tan; Xiaodan Jiang; Ziyuan Liu; Xuemin Li (Frontiers in Cell and Developmental Biology)
The Hippo/YAP pathway is a signaling pathway that plays an important role in cell proliferation, survival, differentiation, cell fate determination, organ size, and tissue homeostasis. Lens epithelial cells (LECs), located on the anterior surface of the lens, are the parental cells responsible for growth and development of the transparent ocular lens. During lens development, LECs undergo a process of differentiation where they exit the cell cycle and transform into lens fiber cells (LFCs), which constitute the majority of the lens structure. YAP is involved in the proliferation and differentiation of LECs, the maintenance of nuclear morphology, cell polarity, cell apical polarity complex, and connexin morphology. The role of the ordered arrangement of LFCs has been demonstrated in several animal studies, and Yap1 heterozygous deletion mice exhibit cataracts. The mechanism of the Hippo/YAP pathway in the physiological activities and lesions of LECs is complex, which is of great significance to understanding the development of the lens and the pathogenesis of lens-related diseases.